Exploring the Symmetry, Structure, and Self‐Assembly Mechanism of a Gigantic Seven‐Fold Symmetric Pd84 Wheel1. Issue 38 (9th July 2014) - Scullion, Rachel A.; Surman, Andrew J.; Xu, Feng; Mathieson, Jennifer S.; Long, De‐Liang; Haso, Fadi; Liu, Tianbo; Cronin, Leroy
Abstract The symmetry, structure and formation mechanism of the structurally self‐complementary Pd84 = [Pd84O42(PO4)42(CH3CO2)28]70− wheel is explored. Not only does the symmetry give rise to a non‐closest packed structure, the mechanism of the wheel formation is proposed to depend on the delicate balance between reaction conditions. We achieve the resolution of gigantic polyoxopalladate species through electrophoresis and size‐exclusion chromatography, the latter has been used in conjunction with electrospray mass spectrometry to probe the formation of the ring, which was found to proceed by the stepwise aggregation of Pd6− = [Pd6O4(CH3CO2)2(PO4)3Na6−nHn]− building blocks. Furthermore, the higher‐order assembly of these clusters into hollow blackberry structures of around 50 nm has been observed using dynamic and static light scattering.